1962
DOI: 10.1177/002383096200500103
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Post-Stress Intervocalic Stops and Preceding Vowels

Abstract: Measurements of the duration of the closure of post-stress, intervocalic stops in two-syllable words, of the vowels that precede them, and of vowels preceding stops in monosyllabic words were made from the speech of one speaker with intervocalic ‘voiced t’. Results for monosyllabic words indicate a vowel duration ratio of 2:3 before voiceless and voiced stops and four intrinsically short vowels, /I, ∊, Λ, U/. The duration ratio of vowels before stops in two-syllable words and those in mono-syllabic words is 2:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
2
3

Year Published

1980
1980
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 6 publications
0
27
2
3
Order By: Relevance
“…The finding that native English speakers produce / t / and / d / in different ways does not contradict other studies. Sharf [19], in a study of bisyllabic words, found that inter vocalic / t / and / d / were produced with a 40-ms difference and that / d / was the longer of the two consonants.…”
Section: Resultsmentioning
confidence: 99%
“…The finding that native English speakers produce / t / and / d / in different ways does not contradict other studies. Sharf [19], in a study of bisyllabic words, found that inter vocalic / t / and / d / were produced with a 40-ms difference and that / d / was the longer of the two consonants.…”
Section: Resultsmentioning
confidence: 99%
“…Requests for reprints should be sent to Dominic W. Massaro is present and may serve as distinguishing features (Lisker, 1977;Massaro, 1975b;Wilder, 1975). In studies measuring the durations of vowels within spoken words, vowels preceding voiced consonants are found to be somewhat longer than the same vowel spoken before the unvoiced cognates (Lehmann & Heffner, 1943;Peterson & Lehiste, 1960;Sharf, 1962;Umeda, 1975). For example, with the words (the) use and (to) use as test material, Denes (1955) found that vowel duration varied from 40 to 80 msec in voiceless Ijusl and from 120 to 200 msec in voiced Ijuz/.…”
mentioning
confidence: 99%
“…Vowels preceding voiceless stops are noticeably shorter in English. The shortening effect of voiceless stops on preceding vowels has been replicated in many studies [Belasco, 1953[Belasco, , 1958Denes, 1955;Peterson and Lehiste, 1960;House, 1961;Delattre, 1962;Sharf, 1962;Wolf, 1978;and many others]. Gussenhoven [2004] understands this effect as enhancement in the sense of Stevens and Keyser [1989].…”
Section: (Usative) Elat(ive) Ess(ive) Gen(itive) Ill(ative) Inesmentioning
confidence: 92%